Asbab Nuzul Qs Al-Hujurat Ayat 13: (Sebuah Metodologis Pendekatan Pendidikan Multikultural) - Inan Tihul (STIT Muslim Asia Afrika, 2021)
The Qur'an that Allah revealed to the Prophet Muhammad was not all at once in the form of a book that we see today. But Allah brought it down gradually. Sometimes it comes down a verse, sometimes half a verse, sometimes several verses, and sometimes a letter. From the point of view of the revelation of the Qur'an, we can distinguish it into two parts. First, the verses that Allah revealed for certain reasons. Second, the verses of the Qur'an that Allah sent down without any specific reasons. The verses that were revealed due to certain reasons are called tasyri'iyah verses or legal verses, namely verses that explain a certain law because there are questions from friends to the Prophet. Furthermore, Allah revealed the Qur'an not only for the Arabs but as a guide for all mankind. Allah does not look at a person based on his appearance, does not look at his ethnicity, but Allah looks at his heart and deeds. The Qur'an does not only talk about the human relationship with Allah (hablumminallah) but also discusses how to interact with others (hablumminannas). Through QS Al-Hujurat verse 13, Allah informs us all that has created us all from male and female types, tribes, nations to know each other. From this we can understand that the Qur'an teaches us to recognize and assess the importance of cultural and ethnic diversity in shaping the lifestyle, social experience, personal identity, educational opportunities of individuals, groups and countries.